Nilai dan Kepercayaan Masyarakat Banjar Terhadap “Air Doa” Dari Tuan Guru (Equilibrium: Jurnal Pendidikan, 2022)
Abstract :The belief in the prayer water from Tuan Guru is a belief in the Banjar community to a Tuan Guru to ask for prayer when they are having a problem in their daily life. Prayer water is water that has been read a prayer by Tuan Guru with the source of prayer based on verses from the Holy Qur'an. The writing in this study aims to find out how the people of Banjar believe in the prayer water read by Tuan Guru and find out the values contained in the prayer water belief.The method used in this study is a qualitative research method, the data source is purposive sampling with an ethnographic approach through observation and interview techniques. The results of this study found: 1) Belief in prayer water in the Banjar community is divided into five namely knowledge about origins, reasons for asking for prayer water, motives for asking prayer water, how to pray for prayer water, taboos on prayer water, and the impact of prayer water . 2) The values contained in the belief in the prayer water of Tuan Guru are three values: First, religious values in the form of prayers. Second, social values, namely the existence of friendship, the attitude of helping each other, the existence of affection, the existence of communication and the presence of courtesy towards the Master. Third, the material value is in the form of monetary gifts and gifts in the form of objects, which are given by the community to Tuan Guru after asking for prayer water. The belief in the water of prayer from Tuan Guru in the Banjar community in the village of Karya Jadi, Tabukan District, Barito Kuala Regency, has existed for a long time which was then passed down from generation to generation until now.Keywords: Faith, Prayer Water, Values
Keywords: Kepercayaan; Air Doa; Nilai